Middle Miocene Depositional Environment Shift in the Tarakan Basin: Some Perspectives from the Onshore Simenggaris Area - Isnianto Saputra; Tulus Wibisono; Avesta Y. Prasetya (Berita Sedimentologi, 2018)
This paper aims to share ideas on the stratigraphic evolution of the Tarakan Basin based on data from the Simenggaris area, onshore NE Kalimantan. Various data sets were incorporated in order to get a robust and comprehensive interpretation, including well logs, cores, and paleontology and petrography analyses. Post-stack time migration 2D seismic data were utilized to generate isopach maps, which were then used as the framework for paleogeographic models.We concluded that the stratigraphic succession in the onshore Tarakan Basin consists of two major depositional environments, with the shift occurring during Middle Miocene. The most significant marker of depositional system transition was observed in the paleontology and lithofacies association. In the Eocene-Early Miocene, the fossils were dominated by foraminifera and by low energy sediments such as shale and limestone with some tuff were also present, typical of a marine depositional system. Meanwhile, in the upper Middle Miocene to Pliocene, the fossils were dominated by pollen species and by siliciclastic sediments like sandstone, shale and coal, which were interpreted as a deltaic depositional environment.